2015
DOI: 10.1111/ajag.12199
|View full text |Cite
|
Sign up to set email alerts
|

Group sessions with Paro in a nursing home: Structure, observations and interviews

Abstract: This study supports other research showing Paro has psychosocial benefits and provides a guide for those wishing to use Paro in a group setting in aged care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
124
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(131 citation statements)
references
References 26 publications
(36 reference statements)
4
124
0
3
Order By: Relevance
“…Past research identified therapeutic benefits emotionally [22, 26], physically [9], behaviourally [28], and socially [9, 21, 23, 24]. The research reported in this paper adds support to these findings for the use of Paro in improving mood, reducing challenging behaviour, and facilitating social interactions.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Past research identified therapeutic benefits emotionally [22, 26], physically [9], behaviourally [28], and socially [9, 21, 23, 24]. The research reported in this paper adds support to these findings for the use of Paro in improving mood, reducing challenging behaviour, and facilitating social interactions.…”
Section: Discussionsupporting
confidence: 68%
“…Those authors did, however, find that Paro had a significant therapeutic impact. Previous work has shown that Paro can alter the psychosocial environment [25] and function as a social catalyst [24] thereby establishing a context where elderly residents are more likely to be receptive to care interventions. The findings of the study described in this paper confirm the positive impact of Paro detailed in early work and suggest that there is even greater scope for its use in the support of residents in aged care facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies involved assessing the effects or perceived impacts or experiences of specific sessions spent with a robopet. These sessions could be facilitated by therapists or researchers (Birks et al, ; Chang et al, ; Giusti & Marti, ; Gustafsson et al, ; Iacono & Marti, ; Moyle et al, ; Robinson, Broadbent, & MacDonald, ) or resident‐led with residents interacting with the robot as they wished. The robots were used in either a group or an individual context, or both.…”
Section: Resultsmentioning
confidence: 99%
“…One professional caregiver reported on an intervention with JustoCat in a care home and highlighted how she perceived an “introverted” resident to have had moments of “‘waking up” and becoming “more aware and alert” (Gustafsson et al, ). Interacting with robopets induced verbal responses with residents talking to the robopets either directly or with others (Birks et al, ; Chang & Sabanovic, ; Giusti & Marti, ; Iacono & Marti, ; Moyle et al, ; Robinson et al, ). Verbal responses were often positive showing appreciation for the robot using words such as “beautiful” and “cute” (Giusti & Marti, ; Iacono & Marti, ; Moyle et al, ; Robinson et al, ).…”
Section: Resultsmentioning
confidence: 99%